'A commons before the sea:' climate justice considerations for coastal zone management. (15th March 2020) - Jurjonas, Matthew; Seekamp, Erin
ABSTRACT: If climate change mitigation and adaptation are a human right, institutional change is needed that considers coastal ecosystem integrity as a common pool resource. Increasing risks in coastal zones necessitates adopting new and frequently controversial zoning, planning, and management practices, particularly as insurance programmes reform or require bailouts. In the U.S., current coastal policy frameworks employed by the Federal Emergency Management Agency (FEMA) and state-level authorities incentivize defensive strategies, especially in high-value tourism destinations, despite critiques of inequity and longer-term evidence demonstrating that hardening shorelines shifts erosion patterns. Other coastal regions and developing countries that cannot afford defensive strategies – particularly rural, minority, and impoverished communities located adjacent to estuarine areas – rely heavily on ecosystem services for protection and will likely disproportionately face buyouts, forced relocation, and retreat as seas rise.